2016
DOI: 10.1186/s40246-016-0096-9
|View full text |Cite
|
Sign up to set email alerts
|

The status of Her2 amplification and Kras mutations in mucinous ovarian carcinoma

Abstract: Jayson GC et al. remarked in Lancet that nearly 100% of mucinous ovarian cancer cases have Kras mutation as well as a high frequency of Her2 amplification. Using the Abbott PathVysion Her2 DNA Probe Kit and Kras mutant-enriched PCR Kits (FemtoPath®), 21 samples of primary ovarian mucinous cystadenocarcinomas from Taiwanese patients were examined to determine the status of Her2 amplification and Kras mutations. Our results showed the Her2 amplification rates were 33.33%, while the Kras mutation rates were 61.90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Concurrent aberrant ERBB2 and KRAS signaling has been observed in a marked number of cases (~11%), suggesting that acquired ERBB2 amplification is secondary to the emergence of KRAS activating mutation (10). Although oncogenic KRAS driver mutations and ERBB2 amplification are not mutually exclusive (15), KRAS mutations may be mutually exclusive with c-MYC amplification (9).…”
Section: Potential Candidate Gene Alterations In Mucinous Ovarian Cancermentioning
confidence: 99%
“…Concurrent aberrant ERBB2 and KRAS signaling has been observed in a marked number of cases (~11%), suggesting that acquired ERBB2 amplification is secondary to the emergence of KRAS activating mutation (10). Although oncogenic KRAS driver mutations and ERBB2 amplification are not mutually exclusive (15), KRAS mutations may be mutually exclusive with c-MYC amplification (9).…”
Section: Potential Candidate Gene Alterations In Mucinous Ovarian Cancermentioning
confidence: 99%
“…mEOC is not associated with BRCA1/2 mutations, whereas approximately 25% of HGSOCs carry either germline or somatic mutations of these genes [12,14]. KRAS mutations are observed in 40-50% of patients, and ERBB2 (human epidermal growth factor receptor 2, HER2) gene amplification has been observed in 20-30% of invasive mEOCs [15,16]. Furthermore, mEOC has been associated with a homozygous loss of the cyclin-dependent kinase inhibitor 2A (CDKN2A) locus, and mutations in genes that activate the mitogen activated protein kinase (MAPK) pathways (such as BRAF, AKT1 and PI3K) [13].…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] After merging the previously reported raw data of HER2 ampli cations, HER2 mutations and KRAS mutations with the new information of BRAF, we identi ed that their corresponding frequencies are 35% for HER2 ampli cations, 35% for HER2 mutations, 60% for KRAS mutations and 80% for BRAF mutations in all 20 MOC Taiwanese patients (Table 1). [9,10] Our ndings also indicated that there was no signi cant difference in the frequency between BRAF mutations and KRAS mutations when they were compared. However, the frequency of BRAF mutations was signi cant higher than that of HER2 ampli cations and HER2 mutations, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…However, except for one case missing residual DNA and lacking of enough extra tumor component, the characteristics of all remaining study materials of all 20 cases of MOC were described in our previous report, including tissue retrieval and DNA preparation. [2,[8][9][10] Additionally, 7 normal ovarian tissues are used as negative controls. The research was conducted according to International Conference on Harmonization guidelines and complied with all applicable regulations for protection of human subjects of research, including review and approval by the Institutional Review Board, Chung-Shan Medical University Hospital Taichung, Taiwan.…”
Section: Methodsmentioning
confidence: 99%